Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3329/bmj.v41i1.18778
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bronchial Asthma Among Secondary School Students in Dhaka City

Abstract: Asthma is a substantial health problem among children and adults worldwide, many countries having increasing prevalence of bronchial asthma. Within our knowledge no epidemiological studies have addressed the burden of bronchial asthma among secondary school students in Bangladesh. This study aimed to determine the prevalence of bronchial asthma and its associated factors among secondary school students. A cross sectional study was conducted from January 2010 to June 2010. Two hundred and fifty secondary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…9 This is comparable to the results of a study from Bangladesh wherein asthma was more prevalent (15.6%) in males as compared to females (7.4%). 16 In contrast to our findings another study from Karachi reported both eczema and allergic rhinitis to be more prevalent in females with a much higher prevalence rate of 54.47% and 59.03% respectively. 11 We observed that the frequency of wheezing was significantly high in children less than 5 years of age followed by the age group 6 to 10 years.…”
Section: Discussioncontrasting
confidence: 99%
“…9 This is comparable to the results of a study from Bangladesh wherein asthma was more prevalent (15.6%) in males as compared to females (7.4%). 16 In contrast to our findings another study from Karachi reported both eczema and allergic rhinitis to be more prevalent in females with a much higher prevalence rate of 54.47% and 59.03% respectively. 11 We observed that the frequency of wheezing was significantly high in children less than 5 years of age followed by the age group 6 to 10 years.…”
Section: Discussioncontrasting
confidence: 99%